Karakteristik Morfologi dan Hasil Kedelai Edamame yang Diberi Eco-enzyme dan Pengendalian Gulma Berbeda di Lahan Tropis - Soverda, Nerty; Swari, Elly Indra; Neliyati, Neliyati; Ratna, Yuni; Pebrianti, Herni Dwinta; Wahyuni, Dilla (Jurnal Media Pertanian, 2024)
Edamame soybeans are a variety of soybeans that act as leaf vegetables that are rich in protein, minerals and vitamins. Edamame soybean cultivation is not yet popular, even though the need and demand is quite large. Eco-enzymes are inputs that play an important role as natural hormones and provide nutrients for plants. Eco-enzyme is an organic product that goes through an anaerobic fermentation process. A decrease in the yield of cultivated plants can be caused by competition with weeds. Several general weed control options have been developed, but appropriate weed control options are needed to ensure production and ecological sustainability. Research was carried out at the Teaching and Research Farm (1Â°370'129" S, 103Â°312'0.501"), Faculty of Agriculture, Jambi University. The research started in January and ended in March 2023 using a split plot design, as the main plot was the concentration of eco-enzymes and the weed control method was chosen as the sub-plot. The eco-enzyme treatments specified were 0 ml L-1(e1), 10 ml L-1 (e2), and 20 ml L-1 (e3). Weed control treatment consists of 2 (two) weed control methods, namely uprooted and cutting off. The parameters observed were morphological growth (plant height, number of root nodules, leaf chlorophyll content, and flowering time) and yield potential (number of pods, number of filled pods, and fresh weight of pods). The results showed that the differences in eco-enzyme concentration and applied weed control were not significantly different on morphological parameters (plant height, number of root nodules, and chlorophyll content of edamame soybean leaves 5 WAP) and yield potential parameters (number of pods, number of filled pods, and wet weight pods) edamame soybeans 65 DAP. Weed control through uprooting was able to increase the number of pods (4.39%), the number of filled pods (5.08%), and the wet weight of the pods (9.57%).Key words: eco-enzymes, edamame soybeans, weed control